Hydrogen production mechanism from biological waste: an overview - Amiza, Abdul Rahman; Masitah, Hasan (Universiti Malaysia Perlis (UniMAP), 2011)
Malaysian International Conference On Trends In Bioprocess Engineering (MICOTriBE) 2009 organized by School of Bioprocess Engineering, Universiti Malaysia Perlis in collaboration with Ministry of Higher Education & Inno Biologics Sdn Bhd, 12th - 13th December 2009 at Dewan Tun Dr. Ismail A, PWTC, Kuala Lumpur, Malaysia.